Kompresi Teks Menggunakan Algoritma Huffman dan Md5 pada Instant Messaging Smartphone Android - M. Taofik Chulkamdi; Sholeh Hadi Pramono; Erni Yudaningtyas (Jurnal EECCIS, 2015)
Instant messaging is one of Android social media application that make user possible to send short messages directly in the same time (real time) using text to another user that online in the some network, more ever a lot of user using this application as an alternative communication via short message service (SMS). Remembering how important this application, so writer make an instant message application with small text transmission that will provide in the current needs with Huffman algorithm application. Writer also make security application model with message digest algorithm (MD5) that used to make the user comfortable so user not distributed by sniffing from another user.Keywords—Huffman, MD5, Instant Message, SMS